BIOSSORÇÃO DE Pb(II) POR CASCA DE URUCUM (Bixa orellana) EM SOLUÇÕES AQUOSAS: ESTUDO CINÉTICO, EQUILÍBRIO E TERMODINÂMICO - Klaiani B. Fontana; Eduardo S. Chaves; Jefferson D. S. Sanchez; Erica R. L. R. Watanabe; Juliana M. T. A. Pietrobelli; Giane G. Lenzi (Química Nova)
This study describes the application of new and low cost biosorbent, shells of urucum (Bixa Orellana), for removal of lead ions (Pb(II)) from water solution. The urucum shells were characterized by Fourier transform infrared spectroscopy and scanning electron microscopy techniques. Batch adsorption experiments were performed in order to evaluate the effect of pH, agitation speed, adsorbent dosage, contact time, temperature, presence of interfering ions and matrix effect on the adsorption of process. The kinetics of biosorption followed pseudo-second-order model. Langmuir and Freundlich isotherm models were applied to describe the biosorption of Pb(II) by urucum shells. The Langmuir model showed better fit and the estimated biosorption capacity was 43.6 mg g-1. The negative Gibbs free energy, ΔG°, confirms the spontaneous nature and positive value of enthalpy, ΔH°, the endothermic character of the process. Furthermore, we also performed an evaluation of matrix and others ions effect on the biosorption process.